Training on Processing Inventory Transactions for Accounting Teachers at the Tangerang City Financial and Institutional Accounting Teacher Association (MGMP) - Minanari, Minanari; Astuti, Retno Puji; Arini, Lusia Sri (CV. Proaksara Global Transeduka, 2024)
Improving the quality of SMK graduates so that they can meet industry needs is one of the objectives of the community service project carried out by the Team in collaboration with MGMP (Musyawarah Guru Mata Pelajaran) Accounting partners and financial institutions in the Tangerang City area. Financial statements function as a tool to analyze financial performance, providing information about financial position, business operations, performance, and cash flow, which can be used as a basis for making economic decisions. The purpose of this service program is to offer assistance and training in interpreting transaction evidence, managing it within the accounting cycle, and producing financial reports. This training includes not only purchase transactions but also various transactions related to sales, cash receipts, cash disbursements, adjusting journal entries, and tax-related matters. One challenge faced by partners is the need for assistance in updating financial accounting standards and taxation standards. The implementation method begins with providing assistance and training in the preparation of Excel-based transactions to enhance partners' understanding and knowledge of accounting. The second stage involves discussing the results of the interpretation of transaction evidence within the accounting cycle and tax treatment. The third stage is the preparation of financial statements as a result of this community service. The outcomes of the community service project indicate an increase in partners' ability to manage business transactions in accordance with current accounting and tax standards.